Follow-up value of serum AFP and aminotransferases in chronic hepatitis B progression - Yu, Mengyao; Huang, Lei; Zhang, Shichang; Jiang, Longfeng; Jin, Yuexinzi; Gu, Min; Liao, Jun; Zhang, Jiexin (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Chronic viral hepatitis (CH) is a stage prior to cirrhosis and primary cancer. Standard protocols for CH assessment during the long follow-up period are of great importance for precise treatment and living quality improvement. In this study, we aimed to analyze multiple serum indexes in chronic hepatitis B (CHB)-infected patients and to discuss their combined values in clinical applications. Methods Total 503 lines of laboratory data from 2012 to 2021 were extracted from103 CHB patients who were followed-up in our hospital. They were divided into the remission group and the progression group according to their complete clinical information and laboratory data. A series of models of serum indexes were analyzed to illustrate the fluctuation trend of @ach index in a time-dependent manner. Results The models revealed that abundant serum alpha-fetoprotein (AFP) in the remission group was characteristically associated with hepatocyte destruction markers aspartate aminotransferase (AST) and alanine aminotransferase and favored a much longer progression-free period (P 0.0001). A model-derived equation consisting of serum AFP and AST values showed a good performance (83% reliability) to distinguish the two groups. Discussion This study clearly demonstrates the intrinsic quantitative relationship between serum AFP and liver aminotransferases involving antivirus treatment response. The model-based equation compensates for serum hepatitis B virus DNA detection during outpatient follow-up and it may serve as a useful laboratory tool for CHB progression assessment.